"Sanitation" in the top development journals: A review - Ma. Laarni D. Revilla; Fangqi Qu; Kallidaikurichi Seetharam; V. V. Bhanoji Rao (Asian Development Bank Institute (ADBI), 2021)
The top 12 development journals published a total of 18,329 papers during the period 2000.2020. Out of these, just 51 focused on sanitation and related issues, which are the focus of this review. Results were mixed on the efficiency of sanitation delivery since political factors and administrative characteristics vary across locations. Accountability and leadership, especially at the local level, appear to be important driving forces. There is a need for more case studies that analyze what works, and what does not, in specific locations. Also, further studies will have to investigate how to influence the norms, traditions, and beliefs towards favorably supporting household sanitation decisions. Additionally, governments should enhance their social welfare programs to address socioeconomic inequalities (i.e., income, gender, and rural-urban disparities), which also critically affect individual and household sanitation investments. Efforts at national and international levels are needed to encourage research on the various dimensions of sanitation.
Keywords: I0; I3; O1; 330; sanitation; sustainable development goals; systematic review; empirical evidence; accountability; health; education; gender